Pelatihan Pembelajaran Berbasis ICT melalui Media Ispring Suites pada Guru MIS, MTs, dan MAS Salman Al-Farisi Liang - Dina Amalya Lapele; Santi Laura Pelenusa (IAIN AMBON, 2023)
ICT learning is learning that is being a great concern in the world of education today. This service aims to provide ICT-based learning training through Ispring Suite media for teachers at MIS, MTsS, and MAS Salman Al-Farisi Liang. The media created is media for learning evaluation. This service is carried out using training methods and workshops. This service consists of 3 stages, namely preparation, implementation, and evaluation. After this service activity was carried out, the teacher was able to make evaluation media using the Ispring Suite media. The teacher gave a positive response and stated that they really needed training like this in the future.Keywords: ICT based Learning, Ispring Suite, Learning Media